2019
DOI: 10.1051/0004-6361/201833970
|View full text |Cite
|
Sign up to set email alerts
|

How do velocity structure functions trace gas dynamics in simulated molecular clouds?

Abstract: Context. Supersonic disordered flows accompany the formation and evolution of molecular clouds (MCs). It has been argued that this is turbulence that can support against gravitational collapse and form hierarchical sub-structures. Aims. We investigate the time evolution of simulated MCs to investigate: What physical process dominates the driving of turbulent flows? How can these flows be characterised? Are they consistent with uniform turbulence or gravitational collapse? Do the simulated flows agree with obse… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 49 publications
1
14
1
Order By: Relevance
“…Important information about the kinematics of the gas are encoded in the slopes of the velocity structure functions. The overall regimes of derived slopes between 0.29 and 0.68 is well within the regime of other observational studies (see, e.g., the compilation in Table 1 of Chira et al 2019). However, while the slopes are similar for 13 CO(1-0), [CI], and 13 CO(3-2) (values between 0.52 and 0.68), the slope of the HISA velocity structure function is flatter with a value of 0.29.…”
Section: Velocity Structure Functionssupporting
confidence: 88%
See 3 more Smart Citations
“…Important information about the kinematics of the gas are encoded in the slopes of the velocity structure functions. The overall regimes of derived slopes between 0.29 and 0.68 is well within the regime of other observational studies (see, e.g., the compilation in Table 1 of Chira et al 2019). However, while the slopes are similar for 13 CO(1-0), [CI], and 13 CO(3-2) (values between 0.52 and 0.68), the slope of the HISA velocity structure function is flatter with a value of 0.29.…”
Section: Velocity Structure Functionssupporting
confidence: 88%
“…Comparing the slopes of observational velocity structure functions (compiled from the literature) with their simulations, Chira et al (2019) conclude that the observed clouds are consistent with an intermediate evolutionary stage that are A44, page 9 of 13 neither purely turbulence dominated (e.g., driven by supernova remnants) nor gravitationally collapsing, but where the gas flows are dominated by the formation of hierarchical structures and cores. The cloud we are observing here around the infrared dark cloud G28.3 appears to be in a similar evolutionary stage.…”
Section: Velocity Structure Functionsmentioning
confidence: 78%
See 2 more Smart Citations
“…Systematic studies of more homogeneous samples of molecular clouds traced in CO found velocity scaling exponents in a range between 0.24 and 0.79 (see Table 2 in Izquierdo et al (2021), which summarizes more than 40 years of observational work). Izquierdo et al (2021) find in their simulations that the scaling exponents lean toward lower values when molecular clouds are dominated by the influence of the Galactic potential rather than the effects of clustered SN feedback and self-gravity (see also Chira et al 2019). This suggests that low velocity scaling exponents are associated with diffuse regions of low star forming activity (e.g.…”
Section: Structure Functionmentioning
confidence: 93%